Creative Performance Self-Efficacy and Mathematical Problem-Solving: Analyzing Students' Strategies in Number Patterns - Fidyani, Okta; Winarni, Sri; Marlina, Marlina; Rohati, Rohati; Kumalasari, Ade (FKIP Universitas Lampung, 2025)
Learning mathematics is important for developing critical thinking and problem-solving skills. However, improving students' creativity and self-confidence is still a major concern, especially in solving complex mathematical problems. This study analyzes the relationship between Creative Performance Self-Efficacy (CPSE) and mathematical problem-solving ability on number pattern material. The research method used is descriptive qualitative, with participants of grade VIII students of Jambi City 1 Junior High Schools selected based on high and low CPSE categories. Data was collected through CPSE questionnaires, problem-solving tests, and semi-structured interviews. The study showed that CPSE is not always directly proportional to mathematical problem-solving ability. Students with high CPSE do not always perform better than those with low CPSE. Some students with low CPSE can develop more systematic and practical problem-solving strategies. In contrast, students with high CPSE have difficulty understanding problems and executing the right solutions. Factors such as conceptual understanding, accuracy, and learning experience also influence problem-solving success. The conclusion of this study confirms that a learning approach that only focuses on improving CPSE is not practical enough without strengthening conceptual understanding and problem-solving strategies. Therefore, a scaffolding-based learning approach, problem-based learning (PBL), and differentiated instruction are needed to accommodate the needs of students with different CPSE profiles. In addition, metacognitive strategies such as self-evaluation, error-based learning to identify errors, and reflective discussions to evaluate solutions are also essential to implement. Keywords: creative performance self-efficacy, mathematical problem-solving, students’ strategies, number patterns.